Content-dependent electroactivity enhancement of nickel hexacyanoferrate/multi-walled carbon nanotubes electrocatalyst: Cost-efficient construction and promising application for alkaline water splitting. (24th January 2020) - Wang, Shuai; He, Ping; He, Mingqian; Jia, Lingpu; Chen, Ning; Dong, Mingfu; Liu, Huanhuan; Wang, Xuejiao; Zhang, Ying; Zhou, Lianhong; Gao, Jun; Lei, Hong; et al.
Abstract: Exploring cost-efficient electrocatalyst towards oxygen evolution reaction is the key to develop sustainable hydrogen energy from water splitting. In this work, based on the different mass contents of MWCNTs, we construct a series of cost-effective noble metal-free NiHCF/MWCNTs (NFM) catalysts for oxygen evolution reaction (OER) in alkaline medium. Thanks to the conductive and 3D interleaved structure of MWCNTs support, the agglomeration of NiHCF nanoparticles is alleviated. NFM catalysts show comparable OER electroactivity with much lower Tafel slope and higher current density than that of bare NiHCF catalyst. In addition, by tuning the content of MWCNTs, as-prepared NFM-2 catalyst shows extensively enhanced electroactivity with the overpotential of only 360 mV at 10 mA cm −2 in 1.0 M KOH solution. Meanwhile, under the optimum mass content of 14.29 wt% MWCNTs, NFM-2 catalyst exhibits long-term stability. The excellent electrocatalytic oxygen evolution performances suggest synergistic effect between NiHCF and MWCNTs. As a result, the content-dependent NFM composites are believed as feasible non-precious electrocatalysts for alkaline OER. Graphical abstract: Image 1 Highlights: Self-assemble NFM catalysts are prepared by facile chemical precipitation. Content-dependent NFM catalysts exhibit superior performance than bare NiHCF. NFM-2 catalyst shows overpotential of only 360 mV at current density of 10 mA cm −2 . Metal hexacyanoferrate is the alternative non-noble metal catalyst towards OER.